PENGARUH MENGHAFAL AL-QUR’AN TERHADAP KEAKTIFAN BELAJAR SISWA ANGGOTA JAM’IYYATUL QURRO’ WAL HUFFADZ DI MTS ALMAARIF 01 SINGOSARI MALANG - Amrul Husni; Anwar Sa’dullah; Mohammad Afifulloh (VICRATINA, 2019)
MTs Almaarif Singosari is an educational institution that combines a National education system and Islamic education. An institution that also develops the potential and interests of the students, including memorizing Al quran. From this, a research objective will be sought that refers to the effect of memorizing al quran students on their learning activeness. This study aims to determine the activities of memorizing students at Mts Almaarif singosari, the activity of students in teaching and learning activities and the effect of memorization on student learning activeness. This type of research is quantitative research, the sample used is a population sample with a total of 30 students as members of the Jam'iyyatul Qurro ’Wal Huffadz. Research instruments using observation sheets, interviews, questionnaires. Before the questionnaire was distributed first, it tested the validity and reliability. The data analysis technique uses simple linear regression test and prerequisite test such as normality test and linearility test. The results of this study Based on the table above obtained a significance value of 0.130 greater than 0.05 and t count 1.558 greater than t table 2.048 then Ha is rejected, Ho is accepted which means there is no effect of variable x on variable y. From the statement above, it can be concluded from the calculation of a simple linear regression test meaning that there is no effect of memorizing the Qur'an on the learning activities of Jam'iyyatul Qurro ’Wal Huffadz member students at MTs Al-Maarif 01 Singosari Malang.